Legal Risk Mitigation in Mutual Fund Sales Through E-Commerce Platforms - Wicaksono, Ageng; Multazam, Mochammad Tanzil (Indonesian Journal of Public Policy Review, 2024)
General Background: E-commerce platforms, such as Tokopedia, have expanded to offer Mutual Fund investments, creating new opportunities in the digital investment space. Specific Background: The sale of Mutual Funds on Tokopedia is governed by OJK Regulation No. 39/POJK.04/2014, aimed at reducing legal risks for investors. Knowledge Gap: There is limited research on how these regulations are applied to protect investors in e-commerce settings. Aims: This study examines the legal risks associated with Mutual Fund sales on Tokopedia and evaluates the effectiveness of existing policies. Results: The collaboration between Tokopedia and a Mutual Fund Securities Agent demonstrates compliance with OJK regulations, enhancing investor protection, reducing transaction costs, and simplifying investment monitoring. Novelty: The research introduces legal issues related to privacy and investment policies within e-commerce platforms. Implications: It highlights the importance of regulatory compliance to ensure investor protection and increase the credibility of digital investment platforms. Highlights: Tokopedia's Mutual Fund sales comply with OJK regulations to protect investors. The absence of transaction fees and ease of monitoring enhances investor convenience. Legal risks in privacy and investment policies are crucial for digital investment platforms. Keywords: Legal Risk, Mutual Funds, E-Commerce, Tokopedia, APERD